Correlation of fluorescence and photocatalytic activity of co-doped tio2 - Lee, Siew Ling (2015)
Co-doped TiO2 (0.5-4 mol%) photocatalysts were synthesized via sol-gel method and their physical and chemical properties were investigated. Addition of Co oxide dopant induced anatase to rutile phase transition and reduced the band gap energy of TiO2. The fluorescence result indicated that the electron-hole recombination rate was reduced with the presence of Co oxide dopant. The best photocatalyst obtained was 3Co-TiO2 which enhanced the photocatalytic activity of TiO2 by 12 folds to 26.6%. The importance of fluorescence properties of Co-doped TiO2 towards its photodegradation of Congo Red was presented.